Evaluation of strategies instituted to improve the tuberculosis control program within Scott Hospital Health Service Area, Lesotho - Makakole, L. (University of Limpopo (Medunsa Campus), 2010)
Background: In spite of the substantial progress made in the development and implementation of many strategies necessary for effective tuberculosis control, the disease continues to be the leading cause of death, and in Africa, because of the expanding HIV epidemic, there has been an increase of HIV associated TB. In 2005 African health ministers declared TB a regional emergency. Although TB treatment is free and Lesotho has 100% DOTS coverage, the country still reported an incidence of 485 per 100,000 population (2005) and a treatment success of 74%, which is still lower than 85% WHO target. Objective: This six-month study at Scott Hospital Health Service area in Lesotho was undertaken to assess the outcome measures of strategies instituted to improve the tuberculosis control programme and determine the effect on TB treatment outcome indicators and TB/HIV integration. xi Methodology: The study design was a quantitative, descriptive study. The principal researcher and a research assistant used a questionnaire to collect data from the outpatient, TB suspect and treatment registers. Study population and sample: The subjects of the study were all adult new sputum- smear positive TB patients enrolled and registered in the Scott Hospital Health Service area TB register from 1st January to 30 June 2006. Results and discussion: A total of 100 new sputum smear positive adult TB patients presenting at Scott Hospital during the research period formed the sample group of this study. This included 47 female and 53 male patients. Their ages ranged from 18 years to 84 years with the mean age of 42 years. Majority 52 (52%) were in the age group 20-39 years, followed by 27 (27%) in age group 40-59 years and 19 (19%) in the age group 60-79 years. There was a high TB/HIV co-infection of 40 (81.6%) among the 49 (49%) who accepted HIV counseling and testing. Active screening of patients for TB resulted in 378 (86.3%) of the 438 TB suspects having their sputa tested. Of these, 100 (26.5%) were new sputum smear positive. Good xii adherence and treatment supervision resulted in sputum conversion rate of 89 (89%). Rigorous implementation of the DOTS strategy showed increased treatment outcomes: cure rate of 76 (76%) and treatment success of 85 (85%). These results were similar to findings of other studies carried out in Cambodia, Tanzania and Rwanda to assess TB programme performance following introduction of improvements. Conclusion: This study demonstrates that implementation of activities consistent with new stop TB DOTS strategy to improve TB control is possible in a rural setting and leads to improvement in TB case detection and treatment success and a decrease in both defaulter and death rates.
Thesis (M Med(Family Medicine))--University of Limpopo (Medunsa Campus), 2010.
Keywords: Tuberculosis; Tuberculosis|xdiagnosis